Exploring the role and value of Pre-Clinical Experiences in a Physiotherapy program in the development of employability skills: a qualitative case series - Susan Edgar; Joanne Connaughton
First and second year undergraduate Physiotherapy students from The University of Notre Dame Australia complete 55 hours of Pre-Clinical Experience (PCE) in the first two years of the program in the lead up to formal clinical placements. Anecdotal evidence from providers has identified the preparedness of students for their formal clinical placements as a result of PCE, however no research has been conducted to date on the outcomes of these experiences as viewed by students. A case series of nine Physiotherapy students utilising focus group methods inclusive of Facebook feedback was employed to examine the experiences of Physiotherapy students and explore their thoughts on the role, outcomes and impact of PCE on their personal and professional development. Results demonstrated the value of early pre-clinical experiences in promoting 'other' personal skills including employability skills. Students valued the opportunity to liaise with professionals whilst also developing an appreciation of the relevance and context of prior learning undertaken at university, through the consolidation of foundational skills. This qualitative case series is a pilot study for a broader survey on the views of Physiotherapy students undertaking pre-clinical experiences during their program of study.